2010
DOI: 10.1002/cm.20490
|View full text |Cite
|
Sign up to set email alerts
|

Arg/Abl‐binding protein, a Z‐body and Z‐band protein, binds sarcomeric, costameric, and signaling molecules

Abstract: ArgBP2 (Arg/Abl-Binding Protein) is expressed at high levels in the heart and is localized in the Z-bands of mature myofibrils. ArgBP2 is a member of a small family of proteins that also includes vinexin and CAP (c-Cbl-associated protein), all characterized by having one sorbin homology (SOHO) domain and three C-terminal SH3 domains. Antibodies directed against ArgBP2 also react with the Z-bodies of myofibril precursors: premyofibrils and nascent myofibrils. Expression in cardiomyocytes of plasmids encoding Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…By day four in culture, premyofibrils bounded by Z‐bodies spaced 1 micron or less apart are evident at the spreading ends and sides of the myotubes, as well as in the central regions of the myotube where a few mature myofibrils can be detected (Figs. a and b) [Rhee et al, ; Sanger et al, ; White et al, ]. One day later in culture premyofibrils continue to form in the elongating ends and along edges of the myotubes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…By day four in culture, premyofibrils bounded by Z‐bodies spaced 1 micron or less apart are evident at the spreading ends and sides of the myotubes, as well as in the central regions of the myotube where a few mature myofibrils can be detected (Figs. a and b) [Rhee et al, ; Sanger et al, ; White et al, ]. One day later in culture premyofibrils continue to form in the elongating ends and along edges of the myotubes (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S10). SORBS2 protein has previously been reported to be present in cardiac but not skeletal muscle (Wang et al 1997;Sanger et al 2010). We used immunohistochemistry (IHC) for protein localization and RT-PCR for RNA expression to examine whether SORBS2 was expressed in skeletal muscle and whether its expression was modified in FSHD biopsies.…”
Section: Tpe-old Modulates Gene Expression In Fshdmentioning
confidence: 99%
“…SORBS2 has previously been detected at the Z-line of cardiac muscle, and overexpression in cardiac cells causes sarcomere disruption (Sanger et al 2010). SORBS2 is also localized at the intercalated disk of cardiomyocytes (Sanger et al 2010) and has been shown to interact with multiple proteins (Roignot and Soubeyran 2009;Lamberti et al 2011;Murase et al 2012;Roignot et al 2014).…”
Section: Sorbs2 Is Activated By Tpe-old In Fshd Myoblastmentioning
confidence: 99%
See 1 more Smart Citation
“…31 It belongs to a small family of adaptor proteins having sorbin homology domains; Sorbs2 is highly expressed in cardiac muscle cells at sarcomeric Z-disc structures, as well as in other cells at actin stress fibers and the nucleus. 31,32 Sorbs2 is considered an adapter protein that plays a significant role in cytoskeletal organization, cell adhesion and signaling pathways. 33 A proteomic analysis of cardiac tissues from patients has suggested that Sorbs2 is released from injured cardiac tissue into the bloodstream upon lethal acute myocardial infarction (AMI).…”
Section: Myosin-3 Myosin-3mentioning
confidence: 99%